Parenthood for childhood cancer survivors: unfounded fear of cancer development in offspring and related health behaviors - Dalkner, Nina; Fleischmann, Eva; Borgmann-Staudt, Anja; Fürschuß, Christine; Klco-Brosius, Stephanie; Kepakova, Katerina; Kruseova, Jarmila; Lackner, Herwig; Michel, Gisela; Mohapp, Andrea; Nagele, Eva; Panasiuk, Anna; et al. (Frontiers in Psychology, 2024)
Current literature reveals no increased risk for adverse non-hereditary health outcomes in the offspring of childhood cancer survivors (CCS), yet survivors reported concerns regarding their offspring’s health. To investigate how the fear of cancer development in offspring influences parental behavior related to health and prevention, survey reports from 256 European adult CCS and 256 age- and sex-matched siblings who participated in a multicenter study on offspring health were analyzed in the present study. Analyses of covariance and chi-square tests were conducted to test for differences between CCS and siblings in outcome variables (all related to healthy parenting behavior). CCS reported higher fear levels (p = 0.044, Partial η2 = 0.01) and less alcohol consumption (p = 0.011, Phi = 0.12) and smoking (p = 0.022, Phi = 0.11) during pregnancy than siblings. In survivor families, children were breastfed less often (p < 0.001, Phi = 0.18). Partial correlation analyses showed that CCS’ fear levels decreased with increasing age (r = −0.16, p = 0.014), time since oncological therapy (r = −0.19, p = 0.003), and number of children (r = −0.21, p = 0.001). Overall, due to their own experiences with cancer, many CCS harbor misperceptions regarding the health outcomes of their offspring. Although the fear decreases with increasing distance from the active disease, any fear should be taken seriously, even if unfounded, and combated through targeted educational measures.